Estimasi Suhu Udara Di Kabupaten Manokwari Melalui Pemanfaatan Citra Satelit Landsat 8 - Mashudi Mashudi; Arif Faisol (Jurnal Meteorologi dan Geofisika, 2022)
Air temperature is the main parameter in determining agricultural land. However, most areas in Manokwari do not have air temperature data due to limited meteorological stations. The utilization of Landsat 8 satellite imagery is one of the alternative solutions for providing air temperature data. This study aims to examine the performance of Landsat 8 satellite imagery in estimating air temperature in Manokwari. The air temperature is estimated using the Normalized Difference Vegetation Index (NDVI) approach. Seven (7) statistical parameters i.e mean error (ME), mean absolute error (MAE), root mean square error (RMSE), relative bias (RBIAS), mean bias factor (MBIAS), percent bias (PBIAS), and the Pearson correlation coefficient (r) are used in the test. Besides, a paired T-test was also used to determine the significance of the difference between the estimated and observed data. A total of 33 Landsat 8 satellite imagery recordings from 2015 to 2020 and air temperature data obtained from the climatological station were used. The results showed that the estimated temperature had good accuracy with ME = 0.50 oC, MAE = 2.73 oC, RMSE = 3.45 oC, RBIAS = 0.09, MBIAS = 1.00, and PBIAS = 9,16% compared with climatological data. Besides, the estimated temperature does not have a significant difference to observed data although it has a weak correlation with r = 0.31. Therefore, Landsat 8 satellite imagery can be used as an alternative solution in providing air temperature in Manokwari for supporting agricultural land development.